Meta-analysis compares the effectiveness of modified biochar on cadmium availability - Liu, Hanyi; Chen, Chuntan; Li, Xue; Yang, Peng (Frontiers in Environmental Science, 2024)
This study aims to quantitatively evaluate the effectiveness of modified biochar in reducing soil Cd availability and Cd content in plants by performing a meta-analysis using data from 58 papers. Modified biochar enhances the surface function and adsorption efficiency of biochar, making it a cost-effective modifier for immobilizing heavy metals. Various factors influence the cadmium (Cd) passivation effect of modified biochar, including the materials used, modification methods, and specific modified materials, warranting further research and clarification. On average, the application of modified biochar results in a significant reduction in soil Cd availability by 65.01% and Cd content in plants by 70.72%. Notably, biochar made from lignocellulose as a raw material exhibits an impressive reduction effect of 96.34% on soil Cd availability. Furthermore, organic modified biochar and acid-base modified biochar demonstrate reduction effects of 119.53% and 112.03%, respectively, for soil Cd availability. When considering plant uptake, modified biochar composed of herbs and combined modified biochar show better Cd reduction effects, with respective reductions of 100.53% and 88.87%. The optimal application rate of modified biochar falls within the range of 2%–3%, leading to a reduction of effective Cd in soil by 76.94% and Cd content in plants by 88.88%. This meta-analysis underscores the potential of modified biochar in remediating Cd-contaminated soil, offering valuable insights for the preparation and application of this material.